2018
DOI: 10.1371/journal.pone.0206942
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular microvesicle microRNAs as predictive biomarkers for targeted therapy in metastastic cutaneous malignant melanoma

Abstract: BackgroundMitogen activated-protein kinase pathway inhibitors (MAPKis) improve treatment outcome in patients with disseminated BRAFV600 mutant cutaneous malignant melanoma (CMM) but responses are of limited duration due to emerging resistance. Although extensive research in mechanisms of resistance is being performed, predictive biomarkers for durable responses are still lacking. We used miRNA qPCR to investigate if different levels of extracellular microvesicle microRNA (EV miRNA) in matched plasma samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
1
33
0
1
Order By: Relevance
“…Subsequently, it was demonstrated that the expression level of miR-497 increases significantly following surgical resection of the primary tumor, indicating that serum miR-497 may be used to evaluate the effect of the surgery, and even as a prognostic index of malignant astrocytoma (16). It was recently reported that miR-497 in extracellular microvesicles is a predictive biomarker of the benefits of mitogen-activated protein kinase pathway inhibitor therapy in patients with metastatic cutaneous malignant melanoma (141). In addition to the aforementioned prognostic indicators, survival analysis may also be used to reflect the prognosis of disease treatment.…”
Section: Clinical Significance Of Mir-497mentioning
confidence: 99%
“…Subsequently, it was demonstrated that the expression level of miR-497 increases significantly following surgical resection of the primary tumor, indicating that serum miR-497 may be used to evaluate the effect of the surgery, and even as a prognostic index of malignant astrocytoma (16). It was recently reported that miR-497 in extracellular microvesicles is a predictive biomarker of the benefits of mitogen-activated protein kinase pathway inhibitor therapy in patients with metastatic cutaneous malignant melanoma (141). In addition to the aforementioned prognostic indicators, survival analysis may also be used to reflect the prognosis of disease treatment.…”
Section: Clinical Significance Of Mir-497mentioning
confidence: 99%
“…In recent years, the regulation of microRNA (miRNA) in various physiological and pathological processes has received increasing attention. 10,11 MiRNAs, which are a class of non-coding nucleotide single-stranded small-molecule RNAs, participate in various biological processes such as cell proliferation, differentiation and apoptosis. 12 In recent years, studies have found that miRNA could be used as a new biomarker in the diagnosis of sepsis.…”
mentioning
confidence: 99%
“…4,19 During therapy, elevated levels of extracellular microvesicle miR-497-5p lead to prolonged progression-free survival in metastatic cutaneous malignant melanoma. 20 According to TCGA database analysis, hsa-miR-497-5p was shown to be down-regulated in GC. Liu et al have reported that knockdown of LINC00662 reduced miR-497-5p expression and decreased GC cell proliferation, while increased the chemo-sensitivity of GC cells.…”
Section: Discussionmentioning
confidence: 99%